An outpatient nursing nutritional intervention to prehabilitate undernourished patients planned for surgery: A multicentre, cluster-randomised pilot study. Issue 8 (August 2020) - van Noort, Harm H.J.; Witteman, Ben J.M.; Vermeulen, Hester; Huisman-de Waal, Getty
Summary: Background & aims: To improve the nutritional status of surgical patients before hospital admission, an Outpatient Nursing Nutritional Intervention (ONNI) was developed. The ONNI comprehends five components: determining causes of undernutrition, performing a nutritional care plan including tailored and general advice, self-monitoring of nutritional intake and eating patterns, counselling and encouragement, and conducting a follow-up telephone call to discuss improvements in nutritional behaviour. Here, we evaluate the feasibility and effectiveness of the ONNI. Methods: In a multi-centred, cluster-randomised pilot study, nurses from outpatient clinics were randomly allocated to usual care (UC) or the ONNI. Patients planned for elective surgery were included if they were at increased risk for undernutrition based on the Malnutrition Universal Screening Tool (MUST) and hospital admission was not planned within seven days. Feasibility outcomes included participation rate, extent of intervention delivery, and patient satisfaction. Nutritional intake was monitored for two days before admission. Body weight, BMI and MUST scores at hospital admission were compared to measurements from the outpatient clinic visit. Data were analysed on an intention-to-treat basis by researchers who were blinded for patients and caregivers. Results: Forty-eight patients enrolled the feasibility phase. Participation rate was 72%. Nurses delivered all intervention components adequately in the end of the implementation period. Finally, 152 patients (IG: n = 66, 43%) participated in the study. A significant difference in mean energy intake (870 kcal/d, 95%CI:630-1109 p < 0.000) and mean protein intake (34.1 g/d, 95%CI: 25.0–43.2; p < 0.000) was observed in favour of the IG. Nutritional energy requirements were achieved in 74% (n = 46) of the IG and in 17% (n = 13) of the UC group (p < 0.000), and protein requirements were achieved in 52% (n = 32) of the IG, compared to 8% (n = 6) of the UC group (p < 0.000). Body weight, BMI and MUST scores did not change in either group. Conclusions: The ONNI is a feasible and effective intervention tool for nurses at outpatient clinics. Patients in the IG had more nutritional intake and fulfilled nutritional requirements significantly more often than patients receiving UC. Further research is required to determine the optimal pre-operative timing of nutritional support and to measure its effect on other patients groups. Clinical trial registration: The study protocol was registered at the ClinicalTrial.gov website with the following identifier: NCT02440165.